Pemetaan Penelitian Rasio Dana Pihak Ketiga (Dpk) Pada Perbankan Syariah Dan Konvensional: Studi Bibliometrik Vosviewer Dan Literature Review - Budianto, Eka Wahyu Hestya; Dewi, Nindi Dwi Tetria; Abidin, Umar Abdillah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2023)
This study aims to determine the research mapping regarding the Third Party Fund (TPF) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the TPF ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the TPF ratio based on the number of clusters and their items; and (3) mapping research topics around the TPF ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 628 journal publications regarding the TPF ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the TPF ratio are divided into 6 clusters and 190 topic items; (3) based on the mapping of literature review studies, there are 5 topics around the TPF ratio. The implications and contributions of this research are to map research topics around TPF ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.